Citizens Charter dan Reformasi Birokrasi - Bambang Wicaksono Triantoro (Magister Ilmu Administrasi Publik, 2004)
Participative, accountable, and travarentpublic service, which honors the rights and the dignity of the citizens, is one among other objectives to be realized by Indonesian bureaucrary as the consequence of the implementation of the autonomy polity. It means that Indonesia bureaucracy should implement new approach, which accommodates new values in providing public services to their costumers, as it is guided by goodgovernance principes. Citizens Charter is one among other strategies which can be utilized to realize participative, accountable and travarentpublic services. This article is aimed to describe the pilot pr eject of the implementation of the Citizens Charter, which was sponsored by Population and Policy Studies Center Gadjah Mada University, in three municipalities, namely: Yogyakarta, Blitar, and Ambarawa. By describing the three cases, the author would like to show that the implementation of Citizens Charter was successfully improved the quality of public services.